A novel technique of blindly positioning bronchial blockers for one-lung ventilation: a prospective, randomized, crossover study - Seihee Min; Susie Yoon; Jiwon Han; Jeong-Hwa Seo; Jae-Hyon Bahk (Journal of Cardiothoracic Surgery)
Abstract Background Several methods for blindly positioning bronchial blockers (BBs) for one-lung ventilation (OLV) have been proposed. However, these methods do not reliably ensure accurate positioning and proper direction. Here, we developed a clinically applicable two-stage maneuver by modifying a previously reported one-stage maneuver for successful insertion of a BB at the appropriate depth and direction in patients requiring lung isolation where a flexible bronchoscope (FOB) is not applicable. Methods This prospective, randomized, crossover study was conducted at a tertiary university hospital and included 94 patients requiring OLV for elective thoracic surgery under general anesthesia. The patients underwent the one-stage maneuver followed by the two-stage maneuver and vice versa, and the success rates of the two methods were compared. After tracheal intubation, the deflated rigid-angle BB was inserted into the endotracheal tube (ET) until a pre-marked point indicating that the BB was just protruding from the ET tip. To identify the carinal depth without FOB, the BB balloon was inflated and advanced toward the intended side whilst monitoring abrupt changes in peak inspiratory pressure and expiratory tidal volume to indicate placement at the carina. In one-stage maneuver, the BB balloon was deflated and advanced 3 cm further from the estimated carinal depth. During the two-stage maneuver, the same procedure was performed to determine the carinal depth, and the deflated BB was withdrawn and reinserted to a predetermined depth with its tip directed 90 degree toward the target bronchus. The accuracy of BB positioning for both maneuvers was evaluated by a 4-point scale, with grades 1 and 2 considered acceptable for providing OLV. Results BB placement was more accurate in the two-stage maneuver than in the one-stage maneuver [88.0% (81/92) vs. 73.9% (68/92), relative risk (95% confidence interval [CI]), 0.45 (0.23–0.88), P < 0.001]. This improvement was particularly significant when targeting the left main bronchus [84.8% (39/46) vs. 58.7% (27/46), relative risk (95% CI), 0.36 (0.17–0.79), P < 0.001)]. Conclusions The novel two-stage maneuver significantly improved the success rate of blindly positioning the BB. Trial registration This study was registered in ClinicalTrials.gov (NCT02981537) on December 05, 2016.